(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The role of Tulepbergen Kaipbergenov – Karakalpakstan’s National Writer, Uzbekistan’s National Writer and titled Hero of the Uzbekistan – in the development of Karakalpak and Uzbek literature is incomparable. T. Qaipbergenov is the true successor of his great ancestors, such as Berdak and Ajiniyaz, who shaped Karakalpak prose, had his own style, created a unique school in Karakalpak literature. As a true child of his people, he was interested in the past, roots, paths, national values, traditions of his country, studied them and skillfully reflected them in his artistic works. Kaipbergenov introduced the Karakalpak people as a nation to the whole world and created works in Karakalpak literature that are equal to world literature.